A comunicação para a saúde na ressocialização e autonomia do cidadão idoso - Françoso, Fernanda Gomes (2010)
This paper deals with the importance of the intersection between communication for health and physical activity as factors of resocialization, improvement of quality of life and autonomy of the needy segment of the elderly. The objective is to verify if the accomplishment of physical activities in group, if the interpersonal communication coming from these activities and the exchange of information about quality of life, disease and health can be considered as relevant factors for the sociability and the improvement of the health of the needy elderly. participate in these opportunities for interaction. This is an exploratory research conducted through the application of a questionnaire, whose interviews were conducted in person, as well as bibliographic research. The main conclusion is that although the elderly deserve access to an interdisciplinary health support network, it is still necessary to emphasize the urgency in organizing care services for this population and a greater emphasis on communication aimed at the elderly. (AU)